2007
DOI: 10.2139/ssrn.1076751
|View full text |Cite
|
Sign up to set email alerts
|

Housing Wealth and Retirement Timing

Abstract: We use data from the Health and Retirement Study (HRS) and the Office of Housing Enterprise Oversight to measure the effect of changes in housing wealth on retirement timing. Using cross-MSA variation in house-price movements to identify wealth effects on retirement timing, we find evidence that such wealth effects are present. According to some specifications the rate of transition into retirement increases in the presence of positive housing wealth shocks. In addition, we use data on expected age of retireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
1
23
0
1
Order By: Relevance
“…(Imbens, Rubin, and Sacerdote 2001), inheritance receipt (Holtz-Eakin, Joulfaian, and Rosen 1993;Joulfaian and Wilhelm 1994;Brown, Coile, and Weisbenner 2010), housing wealth (Farnham and Sevak 2007), and Social Security "notch" cohorts who saw a large change in Social Security wealth (Krueger and Pischke 1992). Holtz-Eakin, Joulfaian, and Rosen (1993); Imbens, Rubin, and Sacerdote (2001); Brown, Coile, and Weisbenner (2010); and Farnham and Sevak (2007) find evidence of labor supply responses to changes in wealth. By contrast, Krueger and Pischke (1992) and Joulfaian and Wilhelm (1994) find little to no response in labor supply and retirement behavior from changes in wealth.…”
Section: Previous Literaturementioning
confidence: 99%
“…(Imbens, Rubin, and Sacerdote 2001), inheritance receipt (Holtz-Eakin, Joulfaian, and Rosen 1993;Joulfaian and Wilhelm 1994;Brown, Coile, and Weisbenner 2010), housing wealth (Farnham and Sevak 2007), and Social Security "notch" cohorts who saw a large change in Social Security wealth (Krueger and Pischke 1992). Holtz-Eakin, Joulfaian, and Rosen (1993); Imbens, Rubin, and Sacerdote (2001); Brown, Coile, and Weisbenner (2010); and Farnham and Sevak (2007) find evidence of labor supply responses to changes in wealth. By contrast, Krueger and Pischke (1992) and Joulfaian and Wilhelm (1994) find little to no response in labor supply and retirement behavior from changes in wealth.…”
Section: Previous Literaturementioning
confidence: 99%
“…Moreover, homeowners having mortgages were less likely to retire (if not yet retired) or more likely to reverse retirement (if already retired). Farnham and Sevak (2016) found that people responded to rising home prices by revising down their expected retirement ages. Specifically, they estimated that a 10% real increase in home value reduced expected retirement ages by about four months.…”
Section: Prior Studiesmentioning
confidence: 99%
“…Previous empirical studies on the effect of house prices, however, find little evidence of wealth effects. For the USA, Farnham and Sevak () find evidence of a housing wealth effect on matched individual–metropolitan‐area house price data, but the impact is highly sensitive to the inclusion or otherwise of state‐level fixed effects. On the other hand, Coile and Levine () and Goda et al .…”
Section: Economic Conditions and Retirementmentioning
confidence: 99%